Recommended Methods to Study Resistive Switching Devices. (27th September 2018) - Lanza, Mario; Wong, H.‐S. Philip; Pop, Eric; Ielmini, Daniele; Strukov, Dimitri; Regan, Brian C.; Larcher, Luca; Villena, Marco A.; Yang, J. Joshua; Goux, Ludovic; Belmonte, Attilio; Yang, Yuchao; et al.
Abstract: Resistive switching (RS) is an interesting property shown by some materials systems that, especially during the last decade, has gained a lot of interest for the fabrication of electronic devices, with electronic nonvolatile memories being those that have received the most attention. The presence and quality of the RS phenomenon in a materials system can be studied using different prototype cells, performing different experiments, displaying different figures of merit, and developing different computational analyses. Therefore, the real usefulness and impact of the findings presented in each study for the RS technology will be also different. This manuscript describes the most recommendable methodologies for the fabrication, characterization, and simulation of RS devices, as well as the proper methods to display the data obtained. The idea is to help the scientific community to evaluate the real usefulness and impact of an RS study for the development of RS technology. Abstract : Resistive switching (RS) studies can build different prototype cells, perform different experiments, display different figures of merit, and develop different computational analyses. Therefore, their real usefulness and impact in RS technologies may be completely different. Herein, the preferred methods to fabricate, characterize, and simulate RS devices are discussed. Studies following these recommendations are expected to be more useful.